2018
DOI: 10.4103/abr.abr_11_18
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Forced Exercise and Bupropion on Chronic Methamphetamine-induced Cognitive Impairment via Modulation of cAMP Response Element-binding Protein/Brain-derived Neurotrophic Factor Signaling Pathway, Oxidative Stress, and Inflammatory Biomarkers in Rats

Abstract: Background:Forced exercise can act as non-pharmacologic neuroprotective agent. In current study, we tried the involved molecular mechanisms of protective effects of forced exercise against methamphetamine induced neurodegeneration.Materials and Methods:Forty adult male rats were divided to Group 1 and 2 which received normal saline and methamphetamine (10 mg/kg) respectively for 30 days. Groups 3, 4 and 5 were treated with methamphetamine for first 15 days and then were treated by forced exercise, bupropion (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…These effects were caused by a significant decrease in superoxide dismutase (SOD), GPx, and glutathione reductase (GR) activity. Another study also reported that the chronic administration of methylphenidate could cause a decrease in SOD, GPX, and glutathione reductase activity levels 23,33,34 .…”
Section: Resultsmentioning
confidence: 94%
“…These effects were caused by a significant decrease in superoxide dismutase (SOD), GPx, and glutathione reductase (GR) activity. Another study also reported that the chronic administration of methylphenidate could cause a decrease in SOD, GPX, and glutathione reductase activity levels 23,33,34 .…”
Section: Resultsmentioning
confidence: 94%